The Influence of Emotional Intelligence, Gender, Residence, and Academic Year on the Academic Performance of Medical Students in Indonesia - Rayhana Rayhana; Dafa Ikhsanudin Ardi; Jihan Samira (Indonesian Journal of Global Health Research, 2025)
Emotional intelligence is an important factor influencing academic performance, especially in high-stress fields like medicine. Medical students face rigorous academic demands, making emotional intelligence crucial for coping and achieving optimal performance. Demographic factors, such as gender, residence, and academic year, may also influence learning experiences. Objective: This study examines the influence of emotional intelligence, gender, residence, and academic year on the academic performance of medical students. A cross-sectional study was conducted from October to December 2023 at a university in Indonesia. The sample selection technique used total sampling, resulting in a sample size of 426 medical students. A structured questionnaire collected demographic data and grade point average (GPA), while the Emotional Competence Inventory 2.0 measured emotional intelligence. Data were analyzed using the Kruskal–Wallis and Mann–Whitney tests. The mean emotional intelligence score was 161.2±19.4, with 8.5% of students in the high category. Age (p=0.013) and academic year (p=0.049) significantly affected academic performance, while residence and emotional intelligence showed no significant effect (p>0.05). Age and academic year had a stronger influence on academic performance than emotional intelligence or residence among medical students.